Focus on the road to modelling cardiomyopathy in muscular dystrophy. Issue 8 (12th July 2021) - Canonico, Francesco; Chirivi, Maila; Maiullari, Fabio; Milan, Marika; Rizzi, Roberto; Arcudi, Alessandra; Galli, Mattia; Pane, Marika; Gowran, Aoife; Pompilio, Giulio; Mercuri, Eugenio; Crea, Filippo; et al.
Abstract: Alterations in the DMD gene, which codes for the protein dystrophin, cause forms of dystrophinopathies such as Duchenne muscular dystrophy, an X-linked disease. Cardiomyopathy linked to DMD mutations is becoming the leading cause of death in patients with dystrophinopathy. Since phenotypic pathophysiological mechanisms are not fully understood, the improvement and development of new disease models, considering their relative advantages and disadvantages, is essential. The application of genetic engineering approaches on induced pluripotent stem cells, such as gene-editing technology, enables the development of physiologically relevant human cell models for in vitro dystrophinopathy studies. The combination of induced pluripotent stem cells-derived cardiovascular cell types and 3D bioprinting technologies hold great promise for the study of dystrophin-linked cardiomyopathy. This combined approach enables the assessment of responses to physical or chemical stimuli, and the influence of pharmaceutical approaches. The critical objective of in vitro microphysiological systems is to more accurately reproduce the microenvironment observed in vivo . Ground-breaking methodology involving the connection of multiple microphysiological systems comprised of different tissues would represent a move toward precision body-on-chip disease modelling could lead to a critical expansion in what is known about inter-organ responses to disease and novel therapies that have the potential to replace animal models. In this review, we will focus on the generation, development, and application of current cellular, animal, and potential for bio-printed models, in the study of the pathophysiological mechanisms underlying dystrophin-linked cardiomyopathy in the direction of personalized medicine. Graphical Abstract: